2017
DOI: 10.1093/ejcts/ezx419
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence for the diagnosis of visceral pleural invasion in non-small-cell lung cancer

Abstract: The sensitivity, specificity and accuracy of visceral pleural invasion diagnosis was improved through the additional use of the autofluorescence mode compared with the white-light mode alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In previous studies, we reported that the use of an autofluorescence endoscopy system improved the diagnostic accuracy rate of VPI (17). VPI is deemed present when the green autofluorescence light is diminished or disappears.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous studies, we reported that the use of an autofluorescence endoscopy system improved the diagnostic accuracy rate of VPI (17). VPI is deemed present when the green autofluorescence light is diminished or disappears.…”
Section: Discussionmentioning
confidence: 97%
“…Based on these facts, it is suggested that sublobar resection should not be performed for cases with suspected VPI even for lung cancer of 2 cm or smaller (3). However, it is difficult to accurately diagnose VPI before and during surgery (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Unfortunately, the conventional intraoperative diagnosis of VPI is time-consuming and prone to inaccuracies, with a reported accuracy of only 56.5%. 5 Consequently, the current gold standard, relying on postoperative pathological diagnosis, 2 introduces a delay in determining an appropriate surgical plan, highlighting the need for a reliable preoperative predictive method for VPI status to ensure precise treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These methods include uorescence spectroscopy (FS) which has been validated as a diagnostic tool during various pathologies, e.g. diastolic dysfunction, 16 non-small-cell lung carcinoma, 17 ischemic heart disease, 18 diabetes mellitus 19 and many others. The method is based on the analysis of the autouorescent substances occurring in the sample (e.g.…”
Section: Introductionmentioning
confidence: 99%